2021
DOI: 10.1084/jem.20200940
|View full text |Cite
|
Sign up to set email alerts
|

Ptpn2 and KLRG1 regulate the generation and function of tissue-resident memory CD8+ T cells in skin

Abstract: Tissue-resident memory T cells (TRM cells) are key elements of tissue immunity. Here, we investigated the role of the regulator of T cell receptor and cytokine signaling, Ptpn2, in the formation and function of TRM cells in skin. Ptpn2-deficient CD8+ T cells displayed a marked defect in generating CD69+ CD103+ TRM cells in response to herpes simplex virus type 1 (HSV-1) skin infection. This was accompanied by a reduction in the proportion of KLRG1− memory precursor cells and a transcriptional bias toward termi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 63 publications
2
16
0
Order By: Relevance
“…We investigated the possibility that these may be tissue-resident T cells (T RM ) that remain in the tissues after inflammation and viral clearance. Neither subset displayed the typical phenotype observed in T RM ( S2 Fig ), where upregulation of CD103 and downregulation of KLRG1 denotes both a tissue-resident and suppressed T cell senescence program, respectively [ 59 , 60 ].…”
Section: Resultsmentioning
confidence: 99%
“…We investigated the possibility that these may be tissue-resident T cells (T RM ) that remain in the tissues after inflammation and viral clearance. Neither subset displayed the typical phenotype observed in T RM ( S2 Fig ), where upregulation of CD103 and downregulation of KLRG1 denotes both a tissue-resident and suppressed T cell senescence program, respectively [ 59 , 60 ].…”
Section: Resultsmentioning
confidence: 99%
“…Whereas the physiological role of T RM is arguably to establish an immunological barrier against infection of the CNS ( 8 , 45 ), these cells can under certain circumstances also contribute to aberrant immune processes. For instance, best evidence that resident immune T cells drive local inflammation comes from studies of skin diseases ( 46 , 47 ). Equally, T RM have been described in lesions of experimental models of CNS autoimmunity ( 21 ) and in human CNS diseases including MS ( 24 , 25 ), but their contribution for tissue damage and disease manifestation remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…KLRG1 and CD103 are both E-cadherin receptors, which are expressed by sensory neurons, satellite glial cells and Schwann cells in sensory ganglia [ 42 ]. Mice studies have indicated that CD8 T RM may develop from tissue-infiltrating KLRG1 − cells [ 43 , 44 ], and that forced expression of KLRG1 impedes T RM formation via inhibitory immunoreceptor tyrosine-based inhibitory motif (ITIM) signals [ 45 ]. These data suggest that repression of KLRG1 is important for normal T RM development and might explain the increased expression of KLRG1 in latently HSV-1-infected human TG.…”
Section: Discussionmentioning
confidence: 99%
“…The hypothesis-driven nature of this technology is a major drawback when new or large sets of markers of interest are newly described. Unbiased technologies like single-cell RNA sequencing in combination with confirmatory in situ analysis is clearly more suitable to study T RM variation within and between tissues and will be used in future studies once widely available [ 25 , 30 , 42 , 45 ].…”
Section: Discussionmentioning
confidence: 99%